2018
DOI: 10.1097/md.0000000000012043
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent talus body fracture with high displacement

Abstract: ARIF with external fixation might be the treatment of choice for such a case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A total of 19 articles of the 176 articles obtained during the initial search met final inclusion criteria for this systematic review ( 4 , 5 , 8 , 9 , 12 - 26 ). There was a 100% agreement between articles included for review without the need for any article to be elevated for tertiary review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19 articles of the 176 articles obtained during the initial search met final inclusion criteria for this systematic review ( 4 , 5 , 8 , 9 , 12 - 26 ). There was a 100% agreement between articles included for review without the need for any article to be elevated for tertiary review.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the nature and impact of pediatric ankle fractures on long-term patient outcomes, including posttraumatic arthritis and alterations to activity level which may impact developmental psychology, these fractures currently pose a significant challenge to orthopedic surgeons and patients alike ( 1 , 3 ). Adding to the complexity of the management of pediatric ankle fractures for orthopedic surgeons, there are several surgical options that exist for anatomical reduction and fixation, including both open and arthroscopic approaches ( 1 - 5 ). Recently, there has been increasing interest in the use of arthroscopic surgery for the management of pediatric ankle fractures ( 4 , 6 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the search strategy and study selection criteria are shown in Figure 1. A total of 12 studies were included in this systematic review [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The average follow-up period varied from 12 to 36 months. Ten studies included Sneppen Type II fractures [11,13,14,[16][17][18][19][20][21][22] and two studies included Sneppen type III [12,15]. Eleven studies included Hawkin's type II fractures 2.…”
Section: Population Characteristicsmentioning
confidence: 99%
“…Talar fracture accounts for 2% of all lower extremities fracture and up to 5% of foot and ankle fracture [4]. Up to 60% of talus surface is covered with articular cartilage, which means that most of the talar body receives its blood supply from the vascular anastomosis around its neck [5,6]. In the last few years, there were many reported cases of rare talar fractures.…”
Section: Discussionmentioning
confidence: 99%